Spinal cord compression in b-thalassemia: follow-up after radiotherapy - Fonseca, Silvana Fahel da (1998)
CONTEXT: Spinal cord compression due to extramedullary hematopoiesis is a well-described but rare syndrome encountered in several clinical hematologic disorders, including b-thalassemia. CASE REPORT: We report the case of a patient with intermediate b-thalassemia and crural paraparesis due to spinal cord compression by a paravertebral extramedullary mass. She was successfully treated with low-dose radiotherapy and transfusions. After splenectomy, she was regularly followed up for over four years without transfusion or recurrence of spinal cord compression. DISCUSSION: Extramedullary hematopoiesis should be investigated in patients with hematologic disorders and spinal cord symptoms. The rapid recognition and treatment with radiotherapy can dramatically alleviate symptoms.